Feasibility Study of Pollutant Removal in Ringlet Reservoir using Lily Canna - Aravind, Akhilash; Fai, Chow Ming; Hua, Chua Kok (International Journal of Engineering and Technology, 2018)
A pilot study utilizing ornamental plants as a pollutant removal agent with varying attributes such as plant density and water conditions was conducted in Universiti Tenaga Nasional, Bangi, Malaysia. Lily canna was selected in this study for its abundance and suitable growth due to ideal Malaysian tropical climates. Lily cannas were placed on floating rafts through a 6-week experimental period in water samples collected from Ringlet Reservoir, Cameron Highlands, Pahang. This study was carried out to investigate the relationship between density of lily canna plants with its corresponding pollutant removal efficiencies. The efficiency of pollutant removal was evaluated in terms of percentage removal of several parameters such as Total Suspended Solids (TSS), Turbidity and Nitrate Concentrations. The results obtained showed that removal efficiencies of up to 83.3% for TSS, 97.8% for Turbidity, 90.7% for Colour, and 85.7% for Nitrate Concentrations could be achieved within the experimental period. The tests were conducted with compliance to standard laboratory tests such as Total Suspended Solids Test, Turbidity Test and Nitrate Cadmium Reduction Method for the determination of nitrate concentrations. To conclude, the quality of treated water proved that lily canna has promising abilities to remove pollutants from water bodies in small communities.